Answer:
The solution for the given algebraic equation is [tex]\frac{ - 2}{71}[/tex]
Step-by-step explanation:
Given algebraic equation as :
[tex]\frac{1}{2}[/tex] ( x - 8 ) + 1 = 2 ( 18 x - 1 )
Now solving the equation while opening the brackets
So, [tex]\frac{1}{2}[/tex] × x - [tex]\frac{1}{2}[/tex] × 8 + 1 = 2 × 18 x - 2
Or, [tex]\frac{x}{2}[/tex] - [tex]\frac{8}{2}[/tex] + 1 = 36 x - 2
or, [tex]\frac{x}{2}[/tex] - 4 + 1 = 36 x - 2
or, [tex]\frac{x}{2}[/tex] - 3 = 36 x - 2
or, [tex]\frac{x}{2}[/tex] - 36 x = - 2 + 3
Or, [tex]\frac{x}{2}[/tex] - 36 x = 1
or, [tex]\frac{x - 72 x}{2}[/tex] = 1
or, [tex]\frac{- 71 x}{2}[/tex] = 1
∴ 71 x = - 2
I.e x = [tex]\frac{ - 2}{71}[/tex]
Hence The solution for the given algebraic equation is [tex]\frac{ - 2}{71}[/tex] Answer